Oxidative stress contributes to abnormal glucose metabolism and insulin sensitivity in two hyperlipidemia models - Bai, Jiefei (Int J Clin Exp Pathol, 2015)
Objective: Lipid metabolism disturbance can result in insulin resistance and glucose intolerance; however, the features of glucose metabolism are still elusive in different dyslipidemia. Our study intended to explore the characteristics and molecular mechanisms of glucose metabolism abnormal in hypercholesterolemia and hypertriglyceridemia models. Methods: Two mouse models were used in this study, one was lipoprotein lipase gene-deleted (LPL(+/-)) mice, and the other was high fat dietary (HFD) mice. Levels of total cholesterol (TC), triglyceride (TG), high-density lipoprotein-cholesterin (HDL-c) and low-density lipoprotein-cholesterin (LDL-c) in serum were measured by full-automatic biochemical analyzer. Intraperitoneal glucose tolerance test (IPGTT) was performed to evaluate insulin sensitivity and β-cell function. Malondialdehyde (MDA) and total superoxide dismutase (T-SOD) levels in serum were measured by colorimetric determination. mRNA expression of superoxide dismutase 1 (SOD1), catalase (CAT), glutathione peroxidase 1 (Gpx1), nuclear factor erythroid 2-related factor 2 (Nrf2a) and peroxisome proliferator-activated receptor-gamma coactivator 1 alpha (PGC-1α) in liver, skeletal muscle, visceral fat and subcutaneous fat were measured by Real-Time PCR. Results: Compared with HFD mice, the levels of serum TG were significantly higher in LPL(+/-) mice, whereas the levels of TC, HDL-c, LDL-c were significantly lower. The plasma glucose levels were increased at each time point of intra-peritoneal glucose tolerance test (IPGTT) in both groups. Furthermore, the level of serum fasting insulin and homeostasis model assessment index-insulin resistance (HOMA-IR) increased with a decreased ISI in both groups. In addition, the plasma MDA of HFD group was higher than that of lipoprotein lipase-deficiency (LPL(+/-)) group, while the activity of T-SOD in HFD group was lower than that in LPL(+/-) group. Real-Time PCR revealed that the expressions of SOD1, CAT and Gpx1 in liver and subcutaneous fat were lower in HFD group than those in LPL(+/-) group, but higher in skeletal muscle and visceral fat. Conclusions: There are different in glucose metabolism between high TG mice and high TC mice. Impaired insulin sensitivity is more serious in HFD mice than that in LPL(+/-) mice. Oxidative stress could contribute to insulin resistance in hyperlipidemia mice.